2007
DOI: 10.1002/bdrb.20108
|View full text |Cite
|
Sign up to set email alerts
|

Two‐generation reproduction study of di‐2‐ethylhexyl terephthalate in Crl:CD rats

Abstract: Increases in liver weights were found in the male and female animals exposed to 0.6% or 1.0% DEHT in the diet. Because there were no accompanying histopathologic changes, this effect was not considered adverse. Significant decreases in feed consumption in the female animals from the groups consuming 1.0% DEHT in the diet during lactation accompanied reduced postnatal pup body weights and rate of weight gain. Reductions in pup body weights later in lactation may also have been due to direct consumption of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Again, no indications of genotoxicity from diverse in vitro tests have been demonstrated. In repeated dose studies, the liver was the primary target organ of DEHT, whereas in developmental studies, only decreased maternal growth was observed with no effect on the fetus or reproduction (Barber & Topping, 1995;Faber et al, 2007;Wirnitzer et al, 2011). For DEHA, repeated dose toxicity studies in animals found reduced body weight gains, but no evidence of carcinogenicity in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Again, no indications of genotoxicity from diverse in vitro tests have been demonstrated. In repeated dose studies, the liver was the primary target organ of DEHT, whereas in developmental studies, only decreased maternal growth was observed with no effect on the fetus or reproduction (Barber & Topping, 1995;Faber et al, 2007;Wirnitzer et al, 2011). For DEHA, repeated dose toxicity studies in animals found reduced body weight gains, but no evidence of carcinogenicity in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Prior investigations into the potential for DEHT to cause developmental toxicity include a rat two generation reproduction study conducted using dietary concentrations of 0.3, 0.6, and 1.0% DEHT (Faber et al, 2007). Consumption of diets containing up to 1.0% DEHT did not affect male or female fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters were measured as described above for the rat study except the laparohysterectomies were carried out on GD 18. Doses used in these studies were based on prior dietary studies (Knapp, 2005; Faber et al, 2007) or dietary levels capable of providing a maximal dose level of 1000 mg/kg/day to the test animals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations